2017
DOI: 10.1371/journal.pone.0183539
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of acromegaly in patients with symptoms of sleep apnea

Abstract: Acromegaly is a rare disease with nonspecific symptoms with acral enlargement being almost universally present at diagnosis. The estimated prevalence is 40–125 cases/million but targeted universal screening studies have found a higher prevalence (about 10 fold). The aim of the ACROSAHS study was to investigate the prevalence of acromegaly and acromegaly comorbidities in patients with sleep apnea symptoms and acral enlargement. ACROSAHS was a Spanish prospective non-interventional epidemiological study in 13 Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
11
0
6
Order By: Relevance
“…However, screening may also be considered in patients with several medical conditions known to be associated with acromegaly such as type 2 diabetes mellitus, carpal tunnel syndrome, debilitating arthritis, hypertension and sleep apnoea. 10 12 Awareness of these comorbidities is critical for early detection of acromegaly.…”
Section: Screening and Diagnosismentioning
confidence: 99%
“…However, screening may also be considered in patients with several medical conditions known to be associated with acromegaly such as type 2 diabetes mellitus, carpal tunnel syndrome, debilitating arthritis, hypertension and sleep apnoea. 10 12 Awareness of these comorbidities is critical for early detection of acromegaly.…”
Section: Screening and Diagnosismentioning
confidence: 99%
“…These results are supported by the observations by Castellani et al, 16 who showed higher uvula thickness and tongue length in acromegaly patients with OSA compared with those without OSA. On the contrary, van Haute et al 3 and Sesmilo et al 17 showed no correlation between severity of OSA and cephalometric parameters. The differences could be attributed to variations in image acquisition and interpretation in these small cohorts.…”
Section: Discussionmentioning
confidence: 91%
“…The mode of imaging used was also different in the various studies. van Haute et al 3 and Castellani et al 16 used MRI for image acquisition, while Ip et al and Parolin et al 8,18 and Sesmilo et al 17 used computed tomography and teleradiography, respectively. This is the first data on acromegaly and SRBD among Indian subjects although there are several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The most common complaints bringing patients with acromegaly to consult their primary care doctors, that lead to further tests to confirm diagnosis are headache and acral enlargement. 14 The latter feature usually comprises of lower jaw enlargement and protrusion (prognathism) with dental malocclusion, overbite and interdental separation 15 and, increasing ring and shoe size. 10 , 16 …”
Section: Methodsmentioning
confidence: 99%